The current situation of English language teaching to the 10 - form students at Dong Hy Secondary School: a case study - Luân, Thị Phương Hảo (ĐHNN, 2017)
Definitions and characteristics of a good communicative activity. Advantages of communicative language teaching. Problems of applying communicative language teaching. Findings and recommendations.